2015
DOI: 10.5959/eimj.v7i2.361
|View full text |Cite
|
Sign up to set email alerts
|

The Graphical Assessment of Multivariate Normality Using SPSS

Abstract: Multivariate analyses depend on multivariate normality assumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 1 publication
0
13
0
4
Order By: Relevance
“…Kim (2013) stated that if the |skewness| > 2 or |kurtosis| > 7, the data did not form a normal distribution. multivariate normal distribution, the Chi-square and Mahalanobis distance plot will form a straight line (Nor, 2015). Figure 2 showed that the variables of this sample formed a multivariate normal distribution.…”
Section: Multivariate Normal Testmentioning
confidence: 80%
“…Kim (2013) stated that if the |skewness| > 2 or |kurtosis| > 7, the data did not form a normal distribution. multivariate normal distribution, the Chi-square and Mahalanobis distance plot will form a straight line (Nor, 2015). Figure 2 showed that the variables of this sample formed a multivariate normal distribution.…”
Section: Multivariate Normal Testmentioning
confidence: 80%
“…After controlling for univariate outliers, Mahalanobis distances revealed no multivariate outliers (Tabachnick & Fidell, 2013). Lastly, univariate normality was checked by visually inspecting the histogram and evaluating skewness and kurtosis of every variable, and multivariate normality was assessed by plotting the Mahalanobis distance and v 2 on a scatter plot (Arifin, 2015). Examination of univariate and multivariate normality indicated non-normal distributions for multiple variables.…”
Section: Resultsmentioning
confidence: 99%
“…Before the hypotheses testing, the reliability of the model and edited data had to be tested within the final sample ( N = 162). Multivariate normality of the six variables (experiential avoidance, identity avoidance, moral avoidance, deficit-value avoidance and advertising avoidance and brand hate) in the research model was assessed by examining the scatter plot of the chi-square values versus the Mahalanobis distances (D 2 ) of all 162 observations, with seven degrees of freedom (Nor, 2015). The analysis suggests multivariate normality, as the scatter plot in Figure 1 shows.…”
Section: Methodsmentioning
confidence: 99%